The carnivorous carnival - Snicket, Lemony (Snicket, Lemony. Series of unfortunate events ;, 2002)
On the run as suspected murderers, the unlucky Baudelaire orphans find themselves trapped in the Caligari Carnival, where they must masquerade as freaks in order to hide from the evil Count Olaf.